Diseño de libros de texto para la enseñanza del inglés: una propuesta curricular - Palomo, Hernán Pereira; Ramos Leiva, Lucía (Colombian Applied Linguistics Journal, 2016)
This article presents the development of research and innovative teaching projects that include the publication of five books for English teaching at elementary and secondary school level with themes of the regional culture in northern Chile. It addresses and attempts to fill a deficit regarding the limited number of topics related to regional culture in books being used in Chile to teach English. The theoretical foundation and methodological work that supports this line of research and educational innovation are presented. This has allowed the publication of five books between the years 2009 and 2014. Finally, it is explained how the books have been distributed in schools, the teacher training stage in the region, and projections of the whole process.